Meningkatkan Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Problem Based Learning pada Mata Pelajaran Pendidikan Agama Katolik Materi Aku Pribadi Unik Kelas IV SDN 2 Nainggolan Tahun Pelajaran 2024/2025 - Tiorisma Sinaga (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The low learning outcomes of students can be attributed to various issues that often arise during the classroom learning process. In Catholic Religious Education, the low performance is indicated by the pre-test scores that did not meet the minimum passing criteria (KKM), with only 47.27% of students, or 11 students, failing to achieve the expected scores. The teaching method used by the teacher was predominantly lecture-based, which resulted in low student participation, with the majority of students being passive and only a small number actively engaging in the learning activities. Based on these issues, this research poses the question: